Treatment of hepatitis C in children and adolescents: our experience to date, current status, and prospects - Pokorska-Śpiewak, Maria; Talarek, Ewa; Aniszewska, Małgorzata; Dobrzeniecka, Anna; Marczyńska, Magdalena (Clinical and Experimental Hepatology, 2026)
The objective of this review was to summarize previous Polish experience in treating hepatitis C virus (HCV) in children with direct-acting antivirals (DAAs) and to describe the current situation and perspectives for future HCV treatment in the pediatric cohort. Children aged at least 3 years were only included in the national Polish therapeutic HCV program on April 1, 2025. However, since 2018, over 200 children and adolescents have been treated with DAAs in noncommercial and commercial trials and real-life programs. Through the current therapeutic program, only adult dosages and formulations of DAAs are available; thus, younger children may not be included. They may, however, receive pediatric formulations donated courtesy of pharmaceutical companies. Screening programs, at least for children at risk of HCV infection, should be implemented to identify candidates for DAA treatment.